Medicamentos genéricos e o perfil de dissolução comparativo - Santos Filho, Ivan José dos (Universidade Federal de São Carlos, 2024)
This study investigates the relevance of comparative dissolution profile in the evalu-ation of generic drugs in Brazil, focusing on ensuring therapeutic equivalence with their reference drugs. Initially, the regulatory requirements of ANVISA are examined to prove bioequivalence through dissolution tests. These tests aim to demonstrate that generic drugs release the active ingredient in a similar manner and within the same timeframe as the reference drug. Statistical analysis of the dissolution test re-sults plays a crucial role in determining the significance of differences observed in the dissolution profiles of the compared products. The research method adopted in this study is a literature review, which includes systematic review of scientific arti-cles, regulatory standards, and relevant technical documents on dissolution profile. This approach provides a comprehensive analysis of the current guidelines and practices in bioequivalence assessment, emphasizing the importance of dissolution tests in ensuring the quality and safety of generic drugs available in the Brazilian market.
Generic medications and the comparative dissolution profile
Keywords: Agência Nacional de Vigilância Sanitária; Medicamentos genéricos; Perfil de dissolução comparativo; Brazilian Health Regulatory Agency; Generic drugs; Comparative dissolution profile; CIENCIAS DA SAUDE::FARMACIA::ANALISE E CONTROLE E MEDICAMENTOS